Oritrophium yacuriense (Astereae, Compositae), an overlooked new species from southern Ecuador - Arnelas, Itziar; Armijos-Barros, J.l.; Calvo, Joel (Phytotaxa, 2017)
Oritrophium yacuriense is described as a new species from the Andes of southern Ecuador. Morphological characters are used in order to distinguish it from the closest species O. repens, which differs mainly in the leaf morphology. The new species occurs in wet herbaceous páramos of the lagoon complex of the Yacuri National Park.